Integration between agile accounting techniques and the sustainable strategic balanced scorecard - حيدر علي جراد المسعودي; علي عباس حمزة القصير (Iraqi Journal for Administrative Sciences, 2024)
The research Adopted on importance subject, which recognize the importance of integration between lean accounting techniques and sustainable Balanced Scorecard, how will reflect the application of these techniques on the perspectives, as well as evaluation the performance before lean thus lean its performance using with optional (value stream, continuous improvement) and evaluate the at other times, there are several results, the most important; there is a integration relationship between lean accounting techniques and perspectives of the sustainable Balanced Scorecard, so that this relationship reflected the Use of lean techniques (value stream, continuous improvement) in a positive way on the perspectives of the sustainable Balanced Scorecard, and as a result achieve strategic performance balanced sustainable, rising final score of (61.337%) before lean to (75.923%) after lean.